The potential link between sugar-sweetened beverage consumption and post-exercise airway narrowing across puberty: a longitudinal cohort study. Issue 13 (30th October 2015) - Emerson, Sam R; Rosenkranz, Sara K; Rosenkranz, Richard R; Kurti, Stephanie P; Harms, Craig A
Abstract: Objective: The prevalence of asthma is rising, presenting serious public health challenges. Recent data suggest that sugar-sweetened beverage (SSB) consumption plays a role in asthma aetiology. The purpose of the present study was to determine whether SSB consumption is linked to post-exercise airway narrowing (predictor of asthma development) across puberty. Design: Participants completed pulmonary function tests, physical activity and dietary habit questionnaires, and an exercise test to exhaustion. Setting: Community in Manhattan, Kansas, USA. Subjects: We recruited ten boys and ten girls from an original cohort of forty participants tested in our laboratory approximately 5 years prior. Participants were aged 9·7 (sd 0·9) years at baseline and 14·7 (sd 0·9) years at follow-up. Results: Pre-puberty, boys consumed 6·8 (sd 4·8) servings/week and girls consumed 6·9 (sd 3·7) servings/week, while post-puberty boys consumed 11·5 (sd 5·3) servings/week and girls consumed 7·7 (sd 4·3) servings/week. Using Pearson correlation, SSB consumption was not significantly related to post-exercise airway narrowing at pre-puberty ( r =−0·35, P =0·130). In linear regression analyses, SSB consumption was significantly related to post-exercise airway narrowing post-puberty before (standardized β =−0·60, P =0·005) but not after (standardized β =−0·33, P =0·211) adjustment for confounders. Change in SSB consumption from pre- to post-puberty was significantly associated with post-exercise airway narrowing post-puberty ( r =−0·61, P =0·010) and change in post-exercise airway narrowing from pre- to post-puberty ( r =−0·45, P =0·048) when assessed via Pearson correlations. Conclusions: These findings suggest a possible link between SSB consumption and asthma development during maturation. Reduced SSB intake may be a possible public health avenue for blunting rising asthma prevalence.